Assessing the Readiness of Eco-Friendly Boats as Sustainable Transportation in Green Canyon, Pangandaran Regency - Ramadhani, Iqlima; Alivia Maharani; Erie Fatimah; Naufal Firdaus; Silviana Apriliyankisi (Journal of Tourism Sustainability, 2025)
The increasing focus on sustainable tourism development underscores the need for eco-friendly transportation to minimise environmental impacts and maximise community benefits. Green Canyon, a leading natural tourism site in Pangandaran Regency, has introduced eco-friendly boats as part of its sustainable tourism initiatives. However, the readiness of this transportation mode has not been systematically assessed. This study aims to evaluate the readiness of eco-friendly boats as a sustainable mode of transportation using a quantitative descriptive method. Data were collected through questionnaires distributed to 150 respondents across three stakeholder groups: local agencies, community members, and tourists. Descriptive statistics were used to analyse perceptions across social, economic, and environmental dimensions. The findings indicate a high level of readiness across all dimensions. Respondents largely agree that eco-friendly boats support environmental conservation, economic inclusivity, and social well-being. The study suggests that further policy support, community training, and environmental monitoring are necessary to strengthen the implementation of sustainable transport at Green Canyon.